2013
DOI: 10.1371/journal.pone.0076123
|View full text |Cite
|
Sign up to set email alerts
|

Collective Response of Zebrafish Shoals to a Free-Swimming Robotic Fish

Abstract: In this work, we explore the feasibility of regulating the collective behavior of zebrafish with a free-swimming robotic fish. The visual cues elicited by the robot are inspired by salient features of attraction in zebrafish and include enhanced coloration, aspect ratio of a fertile female, and carangiform/subcarangiform locomotion. The robot is autonomously controlled with an online multi-target tracking system and swims in circular trajectories in the presence of groups of zebrafish. We investigate the colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 55 publications
(80 reference statements)
1
82
0
1
Order By: Relevance
“…Video image analysis and multi-target tracking was achieved using software developed in MATLAB (R2011a, MathWorks), sampled at 30 Hz [30]. Raw experimental data consisted of two-dimensional Cartesian positions x(t) = [x, y](t) for each fish.…”
Section: Experimental Observations Of Zebrafish Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…Video image analysis and multi-target tracking was achieved using software developed in MATLAB (R2011a, MathWorks), sampled at 30 Hz [30]. Raw experimental data consisted of two-dimensional Cartesian positions x(t) = [x, y](t) for each fish.…”
Section: Experimental Observations Of Zebrafish Pairsmentioning
confidence: 99%
“…Both have found that a small subset of the population, trained with pertinent knowledge, such as the location of a food source, is able to influence the swimming direction of the shoal [22,23]. Effects of controlled external stimuli have also been studied, specifically the use of biomimetic robots (ethorobotics) to elicit responses both at the individual level [24][25][26] and in the collective behaviour of fish shoals [27][28][29][30]. Meanwhile, purely computational studies have explored the dynamic response of biologically inspired mobile agents in the presence of an informed agent or group of agents [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The tracking system, described in detail in [56], used a Kalman filter to track the fish centroid through the five-minute experimental time. Fish tracks were verified and repaired in a MATLAB R graphical user interface (GUI) for analysis.…”
Section: Data Assimilation and Statistical Analysismentioning
confidence: 99%
“…In the context of fish behavior, our research group has contributed to demonstrate the use of robotic fish to & Maurizio Porfiri mporfiri@nyu.edu investigate a number of factors related to social behavior, including the role of tail beat frequency and inter-individual spacing in fish schools (Butail et al 2013(Butail et al , 2014. A variety of biologically-inspired robotic fish have been designed to mimic live species, including mosquitofish (Polverino and Porfiri 2013, b) and zebrafish (Abaid et al 2012;Butail et al 2013Butail et al , 2014Polverino and Porfiri 2013;Spinello et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of biologically-inspired robotic fish have been designed to mimic live species, including mosquitofish (Polverino and Porfiri 2013, b) and zebrafish (Abaid et al 2012;Butail et al 2013Butail et al , 2014Polverino and Porfiri 2013;Spinello et al 2013). While these prototypes mimicked several morphophysiological features of their live counterparts, their size was at least three times larger, thereby constituting a potential experimental confound in the analysis of sociality.…”
Section: Introductionmentioning
confidence: 99%